Primary side control technique for capacitive power transfer system without any wireless feedback - Nutwong, Supapong; Hatchavanich, Nattapong; Sangswang, Anawach; Mujjalinvimut, Ekkachai; Konghirun, Mongkol (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The output voltage of capacitive power transfer (CPT) system will change if the load resistance is varied. This paper presents a method to regulate the output voltage using a controller that is located on the primary side, known as the primary side control technique. It does not require any additional components and wireless feedback, which lowers the cost and complexity of CPT system compared to the conventional control technique. Instead of directly measuring the output voltage on secondary side, it is estimated through the measured capacitor voltage on primary side. Modified sine wave control of the full-bridge inverter is adopted to regulate the output voltage. The proposed control technique is validated by the simulation via PSIM software using the practical parameters of capacitive coupler presented in the literature. Simulation results of the output voltage control against the step change in desired output voltage and load resistance indicate the performance of proposed control technique.